(untitled) (Global Journal of Management and Business Research, 2020)
In this article we intend to broaden the field of knowledge of the Organizational Theory (OT) and organizational studies, opening the action-research universe to acknowledge the diversity of organizational practices of social-community collectives. To this end, the first part shows the theoretical constraints caused by the epistemic coloniality that imposes the model upon the modern organization and productivity, competitiveness, and control as their sole axis of analysis. The second part shows the analytical categories used to understand the organizational practices of social collectives in Mexico. These categories came out of community considerations and practices, which stand for political-epistemic projects not included in the theoretical schemes of organizational modernity.